Do STEM Students Vote? - D'Wayne Bell; Jing Feng; John B. Holbein; Jonathan Smith (Institute of Labor Economics (IZA), 2022)
For decades, pundits, politicians, college administrators, and academics have lamented the dismal rates of civic engagement among students who enroll in courses and eventually major in science, technology, engineering, and mathematics (i.e., STEM) fields. However, the research supporting this conclusion has faced distinct challenges in terms of data quality. Does STEM actually decrease the odds that young people will be actively involved in democracy? This paper assesses the relationship between studying STEM and voting. To do so, we create a dataset of over 23 million students in the U.S. matched to national validated voting records. The novel dataset is the largest known individual-level dataset in the U.S. connecting high school and college students to voting outcomes. It also contains a rich set of demographic and academic variables, to account for many of the common issues related to students' selection into STEM coursework. We consider two measures of STEM participation—Advanced Placement (AP) Exam taking in high school and college major. Using both measures, we find that, unconditionally, STEM students are slightly more likely to vote than their non-STEM peers. After including the rich set of controls, the sign reverses and STEM students are slightly less likely to vote than their non-STEM peers. However, these estimated relationships between STEM and voting are small in magnitude—about the same effect size as a single get-out-the-vote mailer—and we can rule out even very modest causal effects of marginally more STEM coursework on voting for the typical STEM student. We cannot rule out modest effects for a few subfields. Our analyses demonstrate that, on average, marginally more STEM coursework in high school and college does not contribute to the dismally low participation rates among young people in the U.S.
Keywords: I21; I23; D72; 330; youth voting; education; college; STEM; large-scale administrative data